IgG4-related Disease Manifesting as Autoimmune Pancreatitis, Sialadenitis, and Cholangitis: Case Report - Tumelytė, Augustina; Rimkus, Vytautas; Tekoriutė, Paulina; Kupčinskas, Limas (Acta medica Lituanica, 2025)
IgG4-related disease (IgG4-RD) is a rare autoimmune disease which can affect almost any organ. We present a case of IgG4-RD, which manifested as chronic autoimmune pancreatitis with pancreatic insufficiency, severe malnutrition, autoimmune sialadenitis, and cholangitis. After the administration of prednisolone and mycophenolate mofetil, the patient’s condition improved significantly.
Keywords: IgG4-related disease; autoimmune pancreatitis; sialadenitis; cholangitis